PEMBINAAN PERENCANAAN PEMASARAN PRODUK BAGI ANGGOTA PKK ASOKA DIKOTA BATAM - Raymond Raymond (Jurnal Pengabdian Barelang, 2019)
The object to be fostered in this service is the Asoka PKK group located in Tanjung Piayu, a sustainable blue spur housing complex, 1 RW 05, Batam City. In community service this time will be carried out coaching in understanding and making business marketing planning, the method used in community service this time is the first Team Lecturer to give lectures and presentation on business marketing planning theory, both Participants will be given guidance in making business marketing planning, third Participants will be given the opportunity to discuss the problems faced in making a business marketing plan. with the community service program this time contributing in the form of participants able to be skilled in planning business marketing